Continuing Education in Dentistry (Revista Nacional de Odontología, 2014)
Nowadays it is not enough to hold a degree title allowing us to exercise a profession. We all know—indeed, it is obvious—that the socioeconomic environment we operate in has evolved rapidly and dramatically. Greater competition in the job market and training needs that are increasingly more specific and dynamic are driving the demand for specialized learning and are making concepts such as continuing education or lifelong training more important. A health professional must have a calling for continuous education, and if his or her work or other responsibilities make it impossible to undertake a post-graduate specialization, master’s degree or Ph.D., clinical and theoretical diploma courses are the best alternative. Even for those who have a postgraduate qualification, diploma courses offer the opportunity to learn about subjects related to their area of specialty. One significant disadvantage that diploma courses suffer is that the students must be committed to interiorizing, questioning or deeply studying the subjects presented, as most diploma courses do not have the means of assessing the people who will take them, and they become akin to non-formal education. Consequently, they are not always highly regarded in terms of the value they add to the profession. Additionally, there has been a proliferation of diploma courses offered by institutions, which are driven more by economics than by education. As a result, the courses are not of the highest quality and students do not have a chance to fully explore the topics presented. This can be counterproductive, as after finishing a diploma course students will attempt to repeat or use the information and techniques that they have only seen from the perspective of the instructors, with no sort of scientific evidence. This is especially true for those professionals who graduated longer ago. The current climate demands competent workers who have the ability to learn and, when doing a job, not limit themselves to following instructions mechanically; they must consciously think about how to improve the tasks they are performing. They can thus break new ground and take on greater challenges. The benefit of continuous training assumes an investment to face the tests ahead. Its positive aspects include:• Better training, leading to added value for job seeking and, as a result, better access to the labor market.• Updating of knowledge.• Career advancement.• The chance to improve professional, scientific or artistic development.We should therefore be aware that our skills and knowledge must be updated and, in fact, the great advantage of diploma courses is that they can be constantly updated. They move much more quickly than master’s and Ph.D. programs, and cost much less. Another major advantage of diploma courses is that they allow students to network. Given the short but intense nature of the courses, graduates can make contacts that will later be advantageous to them, both personally and professionally. Having a diploma improves our work profiles, in much the same way as another language or specialization in a particular subject. In any case, continuous training is something that we should never forget or neglect. Staying up to date with the latest developments in our professions and undertaking training in necessary skills allows us to climb the career ladder and maintain a good strategic position in the workforce.